Living legends : true tales of extraordinary old-timers - Thorne, Sandy (Melbourne, Victoria : Michael Joseph, 2014)
"Meet fourteen remarkable Australian (and one Kiwi!) jacks and jills of all trades with a wealth of experiences from the good old days to modern times. Hailing from all walks of life, they share their memories with renowned yarn spinner Sandy Thorne in a collection of stories full of wisdom and wit.
Keywords: Australia -- Biography; Australia -- Biography -- Anecdotes; Australian